Влияние восстановительного лечения на показатели ограничения жизнедеятельности, нарушения функциональности и структуры опорно-двигательного аппарата у детей старшего школьного возраста с идиопатическим сколиозом ранних степеней = Effect of rehabilitation on the limitations of life indicators, violation of functionality and structure of the musculoskeletal system in children older school age with idiopathic scoliosis early degrees - Aplevich, V. M.; Gorsha, O. V. (Journal of Education, Health and Sport, 2015)
Aplevich V. M., Gorsha O. B. Влияние восстановительного лечения на показатели ограничения жизнедеятельности, нарушения функциональности и структуры опорно-двигательного аппарата у детей старшего школьного возраста с идиопатическим сколиозом ранних степеней = Effect of rehabilitation on the limitations of life indicators, violation of functionality and structure of the musculoskeletal system in children older school age with idiopathic scoliosis early degrees. Journal of Education, Health and Sport. 2015;5(3):361-372. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46336 http://ojs.ukw.edu.pl/index.php/johs/article/view/3387 https://pbn.nauka.gov.pl/works/715458 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.02.2015. Revised 18.03.2015. Accepted: 21.03.2015. Влияние восстановительного лечения на показатели ограничения жизнедеятельности, нарушения функциональности и структуры опорно-двигательного аппарата у детей старшего школьного возраста с идиопатическим сколиозом ранних степеней Effect of Rehabilitation on the limitations of life indicators, violation of functionality and structure of the musculoskeletal system in children older school age with idiopathic scoliosis early degrees В. М. Аплевич, О. В. Горша V. M. Aplevich, O. B. Gorsha Детская городская поликлиника №1, г. Одесса Украинский НИИ медицины транспорта, клинический отдел медицинской реабилитации, г.Одесса City Children’s Clinic №1, Odessa Ukrainian Scientific and Research Institute of Transport Medicine, Clinical Department of Medical Rehabilitation, Odessa Abstract The results of studies on the use of kinezioteypirovaniya for the regenerative treatment of children school age with idiopathic scoliosis early degrees against the background of hypermobility syndrome. Notes the positive dynamics of radiological - in 56.3% of patients spine deviation decreased by 2-3 degrees Cobb against application of staged kinezioteypirovaniya, pain decreased in more than half of the children. Application of the criteria of the International Classification of functionality (the parameters of vital activity limitation, violation of the functions and structures of the musculoskeletal system) showed a more pronounced positive dynamics in patients with additional use kinezioteypirovaniya back muscles. Key words: idiopathic scoliosis, children, quality of life, rehabilitation treatment, kinezioteypirovanie. Реферат Представлены результаты исследований по применению кинезиотейпирования для восстановительного лечения детей старшего школьного возраста с идиопатическим сколиозом ранних степеней на фоне гипермобильного синдрома. Отмечали положительную рентгенологическую динамику – у 56,3% пациентов отклонение позвоночника уменьшилось на 2-3 градуса по Коббу на фоне применения этапного кинезиотейпирования, болевой синдром уменьшился более чем у половины детей. Применение критериев Международной классификации функциональности (по параметрам ограничения жизнедеятельности, нарушения функции и структуры опорно-двигательного аппарата) показало более выраженную позитивную динамику в группе пациентов с дополнительным применением кинезиотейпирования мышц спины. Ключевые слова: идиопатический сколиоз, дети, качество жизни, восстановительное лечение, кинезиотейпирование.